'A police officer shot a Black man': Racial categorization, racism, and mundane culpability in news reports of police shootings of black people in the United States of America. (5th August 2021) - Shrikant, Natasha; Sambaraju, Rahul
Abstract : The current socio‐political circumstances in the United States (US), constituted by the increasing visibility of police shootings of Black people, present a compelling moment for analysing how news media report about law enforcement, culpability, and racism. This paper conducts a membership categorization analysis of recent news media reports of police shootings of Black people (May 2020–October 2020) and investigates how news media negotiate culpability of agents involved these shootings. Findings illustrate how news reports (1) use the repeated category formulation 'police shooting of a Black man' to imply police are culpable for engaging in racist shootings, (2) upgrade culpability of police officers through adding to racial categorization of victims in ways that foreground victims' moral character (e.g., 'unarmed Black man'), and (3) highlight racism as an explanation for shootings and culpability of police through using racial categorizations for police officers. Overall, news media reports use racial categories as a resource to construct racism as an explanation for police shootings and to construct police officers and policing institutions as culpable for these shootings. Thus, we highlight how race and racism are constitutive of, and inseparable from, culpability in news media reports.